AB0503 The Effect of Corticotropin (ACTH 80 Units Weekly or Biweekly) in Combination with MTX in Newly Diagnosed RA Patients from a Clinical and Structural Perspective as Measured by a CDAI Score and Osteitis, Synovitis, and Erosions on MRI. (9th June 2015) - Gaylis, N.; Needell, S.; Sagliani, J.
Abstract : Background: Acthar Gel is an adrenocorticotropic (ACTH) analogue (1). ACTH gel has been approved by the FDA for the treatment of RA since 1952. Nevertheless, there is limited data on the clinical and structural benefits of using Acthar Gel in the treatment of RA. ACTH consists of 39 amino acids, the first 13 of which may be cleaved to form alpha-melanocyte-stimulating hormone (alpha-MSH). Emerging evidence related to the melanocortin system suggests that ACTH may have mechanisms of action in addition to steroidogenesis.(2) ACTH by virtue of inhibitory influences on cytokine action and inflammatory cell migration has been reported to be effective in multiple inflammatory disorders in humans and adrenalectomized rats (3). This may have significant relevance in the management of inflammatory disorders such as RA. Objectives: To study the effects of Acthar Gel on clinical and structural endpoints in early RA patients Methods: 10 patients with early RA, with a minimum of 6 tender and swollen joints, a CDAI score of >6.0 and with the presence of at least 1 of osteitis, synovitis, or erosions on MRI (Esaote 0.3T) were enrolled in this 24 week, open-label study using 15 mg MTX weekly in all patients and Acthar Gel 80 units weekly or biweekly Results: We report interim results on 10 patients of which 5 patients were dosed weekly with 80 units Acthar Gel and 5 patients were dosed biweekly with 80 units Acthar Gel. Eight of the 10 patients showed a clinical response as measured by improvement in CDAI score as compared to Baseline. Clinical remission was achieved in 2 patients, low disease activity in 3 patients, moderate disease activity in 3 patients, 1 patient remained at high disease activity and 1 patient terminated early due to lack of efficacy (table 1 ). When comparing the two treatment groups (weekly or biweekly dosing), all of the 5 patients who were dosed biweekly not only demonstrated a clinical response including 2 remissions, but they also showed a structural response of regression of synovitis and either regression or nominal change in osteitis as demonstrated by MRI (table 1 ). Of the 5 patients who were dosed weekly there was 1 ET for lack of efficacy and 1 treatment failure. There were no significant changes in erosions on MRI and X-ray in both groups possibly due to the short duration of the study. No significant adverse events noted Conclusions: The results of the interim analysis of 10 patients in this pilot study suggest a clinical and structural benefit using Acthar Gel in combination with MTX in early RA. The steroidogenic effect of Acthar Gel as well as the non-steroidogenic effect through the melanocortin system suggests that further evaluation of the use of Acthar Gel in the many different scenarios of the treatment of RA should be explored. The implications, if proven, could result in more effective treatment of early RA and reduction in the need for step-up biologic therapy. To the best of our knowledge this is the first report of the potential clinical and structural benefit of the use of Acthar Gel in the management of early RA References: Acthar Gel Package Insert. Levine, Drug Design, Development and Therapy 2012:6. Anna Catania, The Scientific World Journal (2010) 10, 1840-1853. Disclosure of Interest: None declared